Office markets & public policy - Jones, Colin, 1949 January 13- (Chichester, West Sussex : Wiley-Blackwell, 2013)
Changing business needs brought about by the information technology revolution in recent decades, as well as the drive toward sustainability, require a complete rethink by urban planners and policy makers about the conservation of historical centers and the types and locations of office buildings. This book analyzes these processes and policy areas, offering a broad, international perspective on the myriad issues involved in office markets, including supply and demand, property investment, spatial structure of local office markets, planning policies, and the long term sustainability of cities.
Introduction -- Market fundamentals -- Submarkets and the changing nature of the traditional central business district -- Decentralisation and edge city office centres -- Investment, risk premiums and office market dynamics -- Public policy and competitiveness -- Green offices, office markets and sustainability -- Market changes and challenges -- References -- Index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Office buildings; Central business districts; City planning; Land use, Urban; BUSINESS & ECONOMICS -- Real Estate -- Commercial; Central business districts; City planning; Land use, Urban; Office buildings; Central business districts; Electronic books; Electronic books